2022
DOI: 10.1002/elps.202100271
|View full text |Cite
|
Sign up to set email alerts
|

A discrete dielectrophoresis device for the separation of malaria‐infected cells

Abstract: Malaria is a serious disease caused by Plasmodium parasites that infect red blood cells (RBCs). This paper presents the continuous separation of malaria‐infected RBCs (iRBCs) from normal blood cells. The proposed method employed the discrete dielectrophoresis (DEP) in a microfluidic device with interdigitated electrodes. Our aim is to treat a sample having high concentration of cells to realize high throughput and to prevent the clogging of the microchannel with the use of the discrete DEP. The discrete DEP fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…On the other hand, f c2 of iRBCs is more or less the same as that of the normal red blood cells. The tendency of the change in f c1 of the infected cells agrees with previous results using interdigitated electrodes [27]. It is also worth noting that for the infected cells, few cells did not exhibit the crossover frequency f c2 up to 80 MHz, which was the limit of our instrument.…”
Section: Dep Experimentssupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, f c2 of iRBCs is more or less the same as that of the normal red blood cells. The tendency of the change in f c1 of the infected cells agrees with previous results using interdigitated electrodes [27]. It is also worth noting that for the infected cells, few cells did not exhibit the crossover frequency f c2 up to 80 MHz, which was the limit of our instrument.…”
Section: Dep Experimentssupporting
confidence: 90%
“…For red blood cells suspended in a low conductivity medium, they show two crossover frequencies of the DEP at which DEP switches between pDEP and nDEP in a low-frequency range (<1 MHz) and high-frequency region (>1 MHz). A few studies have been reported on the effect of the malaria infection on the crossover frequencies [25][26][27][28]. However, the DEP behavior of the malaria-infected cells is still not fully conclusive, in particular at high frequencies where the effect of cytoplasmic conductivity is prominent.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been developed to overcome these limitations, in particular in the development of 'continuous mode' separation whereby cell mixtures are continually sorted by DEP into different outlet channels, preventing the trap-filling associated with batch-mode sorters. However, most attempts generally have low flow rates [18][19][20] through the manufacture of electrodes that extend across the height of a (much taller) channel. There are different approaches to such '3D' electrodes; many groups use insulator-based structures (iDEP) [21][22][23], whereas others use the more conventional microelectrodebased structures, using variations on planar manufacture to form vertical columns that generate fields across the inter-electrode space [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria-infected RBCs exhibit changes to the RBC membrane and cytoplasm. The electrical properties of RBCs before and after infection with Plasmodium falciparum are a function of medium conductivity ( Gascoyne et al, 1997 ; Panklang et al, 2022 ), and membrane conductivity is associated with changes to membrane potential ( Rijo-Ferreira et al, 2020 ). Furthermore, quinine, a long used antimalarial drug, is a K + -channel blocker and alters the electrical conductivity of the cytoplasm ( Duncan et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%